Characterising root branching in response to water availability - Morris, Emily Caroline (2019)
Soil is a complex environment for roots to navigate, in part due to the heterogeneous spread of water and nutrients. Water availability in soil varies on both a micro-scale, large pores have a lower water retaining capacity than small pores, and on a macro-scale, due to macropores and cracks that form in the soil. The aim of this thesis was to improve our understanding of how roots sense and respond to these differences in water availability. X-ray computed tomography (CT) was employed to non-destructively observe how root growth is modified in response to changing water availability in soil. Water availability was observed to significantly alter root architecture. If water availability is higher on one side of the primary root than the other then branches will only form towards the wet side, a response called hydropatterning, and if the root experiences a temporary water deficit branching will stop completely, a response called xerobranching. In order to understand how water availability regulates root branching a genetic study was conducted with Arabidopsis thaliana. Plants that lacked known water transporters were tested for their hydropatterning response. Altering the permeability of plasmodesmata surrounding the phloem leads to a hydropatterning defect. Therefore, it is hypothesised that maintaining the dynamics of a ‘hydro-signal’ is critical for water availability to regulate root branching. The work conducted in this thesis highlights the sensitivity of root architecture to water availability in the soil and the importance of water dynamics in the root.